Precious Property or Magnificent Money? How Money Salience but Not Temperature Priming Affects First-Offer Anchors in Economic Transactions - Leusch, Yannik M.; Loschelder, David D.; Basso, Frédéric (Frontiers in Psychology, 2018)
The present study aims for a better understanding of how individuals’ behavior in monetary price negotiations differs from their behavior in bartering situations. Two contrasting hypotheses were derived from endowment theory and current negotiation research to examine whether negotiators are more susceptible to anchoring in price negotiations versus in bartering transactions. In addition, past research found that cues of coldness enhance cognitive control and reduce anchoring effects. We attempted to replicate these coldness findings for price anchors in a distributive negotiations scenario and to illuminate the potential interplay of coldness priming with a price versus bartering manipulation. Participants (N=219) were recruited for a 2 × 2 between-subjects negotiation experiment manipulating (1) monetary focus and (2) temperature priming. Our data show a higher anchoring susceptibility in price negotiations than in bartering transactions. Despite a successful priming manipulation check, coldness priming did not enhance cognitive control (nor interact with the price/bartering manipulation). Our findings improve our theoretical understanding of how the focus on negotiation resources frames economic transactions as either unidirectional or bidirectional, and how this focus shapes parties’ susceptibility for the anchoring bias and negotiation behavior. Implications for theory and practice are discussed.